The use of dual horizontal wells in gas production from hydrate accumulations - Li, Gang; Li, Xiao-Sen; Yang, Bo; Duan, Li-Ping; Huang, Ning-Sheng; Zhang, Yu; Tang, Liang-Guang (Applied Energy, 2013)
The Pilot-Scale Hydrate Simulator (PHS, 117.8 L pressure vessel) is used to study the methane hydrate dissociation with dual horizontal wells using both the steam assisted gravity drainage (SAGD) and the steam assisted anti-gravity drainage (SAAD) methods. This study is the first time to propose the evaluation and the comparisons of the methane hydrate dissociation using these two methods. Both SAGD and SAAD technique are suitable for recovering gas from the unconsolidated hydrate reservoirs with high permeability. The experimental results indicate that in SAGD, the steam chamber expands and the fluid (gas and water) production process can be divided into three stages: (1) the original water and gas in the vessel are driven towards the well, and only gas is produced, (2) the gas and the original water are produced simultaneously, and (3) the steam chamber expands to the production well, and the hot water is produced. The area with limited temperature increase during the steam injection process corresponds to the hydrate undissociated zone in the reservoir. The hydrate dissociation rate, the gas production rate and the energy efficiency ratio (EER) in both the cases of SAGD and SAAD decrease over time. Comparing with that in SAGD, gas is easier to be produced from the upper production well in SAAD, and the long-term EER in SAAD is also larger. In a word, as a gas-producing method, SAAD seems to be more suitable for recovering gas from the hydrate reservoir than SAGD. (C) 2013 Elsevier Ltd. All rights reserved.